The Effect of Digital Multilingual Thematic Dictionary Toward The Fifth Grade Students' Literacy Skill - Mella Resita Widhiastari; Ni Made Ratminingsih; I Gede Budasi (Linguistic, English Education and Art (LEEA) Journal, 2023)
This research aimed to discover whether using a digital multilingual thematic dictionary significantly affects fifth-graders' literacy skills. The author applied pre- and post-test control groups alone for its quasi-experimental design. The researcher used a multi-stage sampling technique to select the research sample. The stage consist of three steps namely: (1) determining population; (2) placement of the sampling area using the statistical matching technique proposed by Fraenkel, J.R., Wallen, N.E., and Hyun, H.H. (2012); and (3) selection of the control and experimental groups via lottery. Students in the 5A grade from SD N 1 Seririt served as the control group and fifth-graders from SD N 1 Kubutambahan served as the experimental group for the sample. The research instruments featured teaching scenarios for the control and experimental groups as well as literacy competency exams with pre- and post-test questions. The pre-test was administered before of treatment, and the post-test was done afterwards. Three treatment sessions were provided to each group using three different treatment lesson materials namely: daily activities, my school, and clothes. The acquired data were quantitatively examined using N-Gain score test analysis, inferential statistics, and descriptive statistics. Based on the findings of the N-Gain Score test computation and the descriptive analysis, the experimental group's mean N-Gain score was 70.5453%, whereas the control group's mean N-Gain score was 67.9676%. The use of multilingual thematic printed dictionaries in the control group and multilingual thematic digital dictionaries in the experimental group shared the same effect, particularly regarding that they were "moderately effective " to enhance the literacy skills of class students, according to the results of the N-Gain score test, which showed that the experimental group's average score was 70.5% and the control group's average was 68%. Hence, it is proven that multilingual thematic dictionaries, both printed and digital, have a significant impact on fifth-graders' literacy skills. Keywords: literacy skills, young learner, digital multilingual thematic dictionary